Enhancement of Cognitive Benefits and Anti-Anxiety Effects of Phytolacca americana Fruits in a Zebrafish (Danio rerio) Model of Scopolamine-Induced Memory Impairment - Lucia-Florina Popovici; Ion Brinza; Florentina Gatea; Georgiana Ileana Badea; Emanuel Vamanu; Simona Oancea; Lucian Hritcu (Antioxidants)
Phytolacca americana fruits exhibit a wide range of biological activities, including antimicrobial, anti-inflammatory, and anticancer properties. This study aims to investigate the phenolic profile of hydroethanolic extracts from both fresh (PEC) and dried (PEU) fruits of P. americana using high-performance liquid chromatography (HPLC) and to evaluate their impact on anxiety-like behavior, memory, oxidative stress, and cholinergic status in zebrafish (Danio rerio, Tübingen strain) treated with scopolamine (SCO, 100 μM). Acute administration of PEC and PEU (0.1, 0.5, and 1 mg/L) was conducted for one hour per day. In silico analyses were performed to evaluate the pharmacokinetic characteristics of the phenolic compounds discerned in the two extracts, using platforms such as SwissAdme, Molinspiration, ProToX-III, AdmetLab 3.0, PKCSM, and PASS. Anxiety-like behavior and memory performance were assessed through specific behavioral assays, including the novel tank test (NTT), light/dark test (LD), novel approach test (NAT), Y-maze, and novel object recognition (NOR). Subsequently, the activity of acetylcholinesterase (AChE) and the extent of oxidative stress in the zebrafish brain were investigated. Our findings suggest that both PEC and PEU possess anxiolytic effects, alleviating SCO-induced anxiety and enhancing cognitive performance in amnesic zebrafish. Furthermore, these extracts demonstrated the ability to mitigate cholinergic deficits by inhibiting AChE activity and supporting antioxidant defense mechanisms through increased activity of antioxidant enzymes and reduced lipid and protein peroxidation. These results highlight the potential use of P. americana fruit extracts in managing anxiety and cognitive impairments related to dementia conditions.